Analysis of Brinjal Germplasm for Resistance to Fusarium Wilt Disease - Akanksha Pandey (Current Perspectives in Agriculture and Food Science Vol. 4, 2023)
Fusarium wilt, caused by Fusarium oxysporum, is a major constraint in brinjal production in India. The disease is widely distributed in tropical, subtropical and some warm temperate regions of the world. The pathogen is difficult to control since it is soil-borne and has a wide host-range, including several hundred species representing 44 families of plants. Infection is through root-to-root transmission, movement of soil and dissemination by farm implements, and insect transmission. A total Fifty two lines of brinjal germplasm were screened against the in a sick plot for fusarium wilt resistance at Develeela life science Pvt.Ltd. Raipur Chhattisgarh. six lines, viz., AB-2, AB-6, AB-8 , AB-24, AB-35, AB-50 showed highly resistant reaction, with no wilting of plants; five lines, viz., Ab-26, AB-25, AB-52, AB-44 and AB-13, showed resistance reaction per cent wilt 3.33 10.0. Two lines, AB-33 and AB-20, displayed a moderately resistant reaction, with wilt incidences of 11.0 and 12.0%, respectively; in contrast, 25 lines were "moderately susceptible to highly susceptible," with wilt incidences ranging from 25.45 to 100.0%.